Kommerell's Diverticulum With a Twist: A Case of Recurrent Wheeze in an 8-Year-Old Boy. (December 2019) - Robles, Tiffany Amber; Srinivasan, Aditya; Mazur, Lynnette; Gourishankar, Anand
Kommerell's diverticulum is a rare, congenital aortic arch anomaly, usually associated with other vascular abnormalities. When present with a concurrent right-sided aortic arch and an aberrant subclavian artery, this triad can form a vascular ring that encompasses the trachea and esophagus. This anatomical variant is usually asymptomatic but can present with respiratory symptoms due to compression of the trachea. In this report, we discuss a case of a Kommerell's diverticulum, which presented as frequent and recurring asthma exacerbations in a pediatric patient.